2022
DOI: 10.3390/clockssleep4040056
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of Ultrastructure of Mice B16 Melanoma Cells under the Influence of Different Lighting Regimes

Abstract: Circadian rhythms of physiological processes, constantly being in a state of dynamic equilibrium and plastically associated with changes in environmental conditions, are the basis of homeostasis of an organism of human and other mammals. Violation of circadian rhythms due to significant disturbances in parameters of main environmental effectors (desynchronosis) leads to the development of pathological conditions and a more severe course of preexisting pathologies. We conducted the study of the ultrastructure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Thus, scientific findings have already demonstrated that B16 under low dosage of light regime preserve characteristic of this tumor like intact tissue safe junctions, functionally active cells with highly irregular nuclei, developed organelles and a relatively low content of melanin. But in contrast the B16 melanoma tissue structure and the ultrastructure under the action of high constant lighting exhibits accelerated growth, increased melanin levels, as significant number of cells in the state of apoptosis and necrosis, like signs of embryonization with background of adaptation to oxygen deficiency [69]. For example, the mice genes, tyrosinase (tyr) [28,70] , solute carrier family 45 member 2 (SLC45A2) [28,71] solute carrier family 24 member 5 (SLC24A5) [28,72] melanopsin, (OPN4) and , rhodopsin, (OPN2) have been identified withal important role in the production of melanin in B16-F10 and Melan-a cells (Table 2) [27,28,73].…”
Section: Characteristic Of B16 and Melan-a Cells Under Influence Of D...mentioning
confidence: 94%
“…Thus, scientific findings have already demonstrated that B16 under low dosage of light regime preserve characteristic of this tumor like intact tissue safe junctions, functionally active cells with highly irregular nuclei, developed organelles and a relatively low content of melanin. But in contrast the B16 melanoma tissue structure and the ultrastructure under the action of high constant lighting exhibits accelerated growth, increased melanin levels, as significant number of cells in the state of apoptosis and necrosis, like signs of embryonization with background of adaptation to oxygen deficiency [69]. For example, the mice genes, tyrosinase (tyr) [28,70] , solute carrier family 45 member 2 (SLC45A2) [28,71] solute carrier family 24 member 5 (SLC24A5) [28,72] melanopsin, (OPN4) and , rhodopsin, (OPN2) have been identified withal important role in the production of melanin in B16-F10 and Melan-a cells (Table 2) [27,28,73].…”
Section: Characteristic Of B16 and Melan-a Cells Under Influence Of D...mentioning
confidence: 94%